Protein-enriched intermittent meal replacement combined with moderate-intensity training for weight loss and body composition in overweight women - Qisijing Liu; Yi Guo; Bo Peng; Dancai Fan; Jing Wu; Jin Wang; Ruican Wang; Jing-Min Liu; Jian Wu; Shuo Wang; Yanrong Zhao (Scientific Reports)
Abstract The global rise in overweight and obesity has been exacerbated by sedentary lifestyles and suboptimal dietary habits. Traditional weight loss methods often struggle with adherence due to restrictive diets and metabolic adaptations. Intermittent meal replacement (IMR), incorporating formulated protein-enriched nutritional shakes, has emerged as a potential strategy for weight management. However, its combined effects with moderate-intensity continuous training (MICT) remain underexplored. This study aimed to evaluate the impact of a weight loss method incorporating formulated protein-enriched nutritional shake IMR in conjunction with MICT workout for overweight female adults. This 8-week parallel randomized controlled trial investigated the impact of protein-enriched IMR combined with MICT on weight loss and body composition in overweight female adults. Participants were randomly assigned to either the MICT group or MICT + IMR group. Body composition, hematological, and urinary biomarkers were assessed pre- and post-intervention. The MICT + IMR Group achieved a greater reduction in body weight (-3.70 kg vs. -1.17 kg, p < 0.001) and body fat mass (-2.25 kg vs. -1.19 kg, p < 0.001) compared to the MICT group. Additionally, fasting blood glucose and insulin levels significantly improved in the MICT + IMR Group, suggesting enhanced metabolic regulation. IMR, when combined with MICT, is a viable strategy for short-term weight loss in overweight women, offering improved fat reduction and metabolic benefits compared to exercise alone. Trial registration: Chinese Clinical Trail Registry, ChiCTR2300076750. Registered 17 October 2023, https://www.chictr.org.cn/bin/project/edit?pid=197611 .